Concentrated evolutionary novelties in the foot musculature of Odontophrynidae (Anura: Neobatrachia), with comments on adaptations for burrowing - Blotto Acuña, Boris Leonardo (2017)
We studied the foot musculature of the fossorial family Odontophrynidae (composed of the genera Macrogenioglottus, Odontophrynus, and Proceratophrys) plus several outgroup taxa from Hyloidea and other burrowing taxa from across Anura. We found novel character-states supporting the monophyly of Odontophrynus, Proceratophrys, and Odontophrynus + Macrogenioglottus. The character-states observed in O. cultripes support conflicting phylogenetic positions within Odontophrynus. A comparison of some novel character-states with a diverse sample of burrowing taxa suggests that some modifications of the foot musculature might be involved in digging.